A study of transient and steady-state regions from single-track deposition in laser powder bed fusion. (January 2021) - Shrestha, Subin; Chou, Kevin
Abstract: The surface morphology of parts made by the laser powder bed fusion (L-PBF) process is governed by the flow of the melt pool. The nature of the molten metal flow depends on the material properties, process parameters, and powder-bed particles, etc., and may result in potentially significant variations along a laser scanning path. This study investigates the formation of transient and steady-state zones through a single-track l -PBF experiment using Inconel 625 powder. Single tracks with lengths of 1 mm and 2 mm were fabricated using 195 W laser power and scan speeds of 400 mm/s or 800 mm/s. The surface morphology of the track was analyzed using a white light interferometer (WLI), and an individual single track can be divided into three distinct zones based on the track width and height. The initial transient region has a wider and taller solidified track geometry, the region near the end of a scan has a tapered profile with a decreasing track width and height, while the steady-state region in the middle has a smaller variation in the width and height. A mesoscale numerical model was further developed using FLOW-3D to examine the formation of the transient and steady-state zones. At the start of a scan, strong flow occurs outward and backward, leading to the formation of a wider track with a bump. As the scan continues, the thermal gradient stabilizes, leading to a steady state, which resulted in a very small fluctuation in the width. Furthermore, the tapered end of the scan track is due to the half-lemniscate shape of the melt pool during laser scanning.